VOLUNTEERING AMONG OLDER MIDDLE-AGED SINGAPOREANS: A LATENT CLASS ANALYSIS. (11th November 2018) - Cheng, G; Chan, A
Abstract: Volunteering has various health and social benefits. The Singapore government has implemented the National Senior Volunteerism Movement with a target to recruit an additional 50, 000 older volunteers. However, local data on factors of volunteering is lacking. Also, existing research has primarily focused on formal volunteering and overlooked informal volunteering, and has typically adopted a global measure of volunteering without differentiating different volunteering activities. To address these gaps, we conducted latent class analysis to examine the volunteering profile among late middle-aged Singaporeans (n=1629). Based on 22 volunteering activities, we identified 3 classes of volunteers: formal-networking, informal-routine-household, and non-volunteers. Subsequent multinomial logistic regression revealed that gender, education level, work status, social networks, social participation, depressive symptoms, psychological resilience, and religiosity differentiated these 3 classes. These findings are discussed with reference to the resource theory, and some local initiatives targeted at older persons.